USING DEONTIC MODALITY IN MAZE RUNNER (THE DEATH CURE) MOVIE - Faisal, Muhammad; Syahri, Chaidir (PROJECT (Professional Journal of English Education), 2019)
The objectives of this research are to identify the types of deontic modality and the meaning of utterances that found in The Maze Runner (The Death Cure) movie. This research used script only from the movie entitled The Maze Runner (The Death Cure) that had been analyzed by the researcher. The research used descriptive as a research design and qualitative method as a research methodology. Therefore, the data of this research was in the form of utterances that was performed by the cast in The Maze Runner (The Death Cure) movie. The research data were collected by taking the movie script from the internet. The collected data were analyzed by Saeed’s theory. The finding revealed that there are two types of deontic modality found in utterances performed by the cast of The Maze Runner (The Death Cure) movie namely; Obligation and permission. The meaning of utterances that belongs to obligation means that someone have to do what the speaker said. While the meaning of utterances that belongs to permission means that someone’s incumbency to authorized somebody else to do something. Keywords:  Deontic modality, The Maze Runner (The Death Cure), Semantics